Ritual Domestikasi Padi Lokal dalam Budaya Sasak-Lombok - Saharudin Saharudin (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
The rice plant for Indonesia, especially in Lombok, is considered unique, not only as a production crop but also as a sacred plant. From the process of planting to harvesting, this plant is treated specially with rituals with religious nuances. This study aims to describe the socio-cultural symptoms of local rice domestication rituals among traditional farmers in Lombok. Based on this description, it is hoped that the views, knowledge, values, and rules will become the reference for the behavior of the rural Sasak people as growers of local rice types. The approach used to achieve this goal is a phenomenological approach. Primary data of this study were obtained through in-depth interviews (structured and non-structured to informants) and participatory observation. The results showed that the local rice domestication ritual is a form of awareness of the cultural-religious views of the local community by combining local knowledge and religious knowledge (Sufistic teachings, as represented in the mantra of planting rice and the concept of pare anak iwoq or orphan rice in pare pemol or rice starter/marker) as a manifestation of the awareness of the Supreme Being and the cosmos. This awareness of the Supreme Being and the universe becomes a reference for local farmers in their behavior, especially in agriculture. With these two types of consciousness, they are guided and directed toward safety, security, and balance.